Cryptosporidium parvum and Enterocytozoon bieneusi in American Mustangs and Chincoteague ponies - Wagnerová, Pavla; Sak, Bohumil; McEvoy, John; Rost, Michael; Sherwood, Dawn; Holcomb, Kevin; Kváč, Martin (Experimental parasitology, 2016)
The prevalence of Cryptosporidium and microsporidia in feral horses, which have minimal contact with livestock and humans, is not currently known. We report the findings of a study on Cryptosporidium and microsporidia in 34 Mustangs and 50 Chincoteague ponies in the USA. Fecal samples were screened for presence of Cryptosporidium spp. by analysis of the small-subunit rRNA (SSU) and 60-kDa glycoprotein (gp60) genes, and Enterocytozoon bieneusi and Encephalitozoon spp. by analysis of the ribosomal internal transcribed spacer region (ITS). Cryptosporidium spp. and E. bieneusi were detected in 28/84 (33.3%) and 7/84 (8.3%) samples, respectively. Sequence analysis of SSU and ITS revealed the presence of Cryptosporidium parvum (n = 20) and E. bieneusi genotype horse 1 (n = 7), respectively. Subtyping of C. parvum isolates at the gp60 locus showed the presence of subtype IIaA17G2R1 in Mustangs and subtypes IIaA13G2R1 and IIaA15G2R1 in Chincoteague ponies. Enterocytozoon bieneusi genotype horse 1 was detected in Mustangs (n = 2) and Chincoteague ponies (n = 5). No Cryptosporidium or E. bieneusi positive animals had diarrhea. The finding that Mustangs and Chincoteague ponies are host to the zoonotic pathogen C. parvum suggests that their infrequent contact with humans and livestock is sufficient to maintain transmission; however, we should also consider the possibility that C. parvum is an established parasite of Mustangs and Chincoteague ponies that persists in these animals independently of contact with humans or livestock.
Keywords: glykoproteiny; Animals; Zoonoses; RNA ribozomální; Genotype; feces; Feces; zoonózy; Prevalence; Feral horses; Cryptosporidium parvum; nemoci koní; SSU; Cryptosporidiosis; divoká zvířata; lidé; mikrosporidióza; genotyp; Glycoproteins; koně; gp60; mezerníky ribozomální DNA; Horses; Phylogeny; RNA, Ribosomal; prevalence; Spojené státy americké; Microsporidiosis; Animals, Wild; Enterocytozoon; United States; kryptosporidióza; DNA, Ribosomal Spacer; zvířata; fylogeneze; Microsporidia; ITS; Horse Diseases; Cryptosporidium; Humans